Computed Tomography Enterography: Quantitative Evaluation on Crohn's Disease Activity. (22nd July 2018) - Cheng, Jingyun; Xie, Hui; Yang, Hao; Wang, Ke; Xu, Guobin; Wu, Guangyao
Abstract : Objective . To explore the feasibility of computed tomography enterography (CTE) in the quantitative evaluation of the activity of Crohn's disease (CD). Methods . There were 49 CD patients with whole clinical, enteroscopy, and CTE data to be analyzed retrospectively. The patients were graded as inactive (0–2), mild (3–6), and moderate-severe group (>6) based on simplified endoscopic activity score for Crohn's disease (SES-CD). The differences in bowel wall thickening, mural hyperenhancement in the portal vein period, and the ΔCT values were analyzed among groups using ANOVA (analysis of variance) and q test. Then, the parameters were correlated with SES-CD, C-reactive protein (CRP), and erythrocyte sedimentation rate (ESR). Results . In the 49 patients, 13 ones were inactive, 19 ones were mild, and 17 ones were moderate-severe; the thickness of bowel wall, mural hyperenhancement in the portal vein period, and ΔCT value among groups were all significantly different (P < 0.001 in all). Correlative analysis showed that compared with the SES-CD, the bowel wall thickening (r = 0.564, P < 0.001 ), mural hyperenhancement in the portal vein period (r = 0.585, P < 0.001 ), and ΔCT value (r = 0.533, P < 0.001 ) were moderately correlated. Conclusion . The mural hyperenhancement in the portal vein period, bowel wall thickening, and ΔCT value can accurately and quantitatively assess the activity of CD lesions and are potential visual biomarkers of CD lesions.